Formulation and Effectiveness Study of an Organic Lotion Based on Mangosteen Peel Extract (Garcinia mangostana L.) on Skin pH - Meiti Rosmiati (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2026)
Mangosteen (Garcinia mangostana L.) peel extract contains xanthones, a class of bioflavonoids known for their antioxidant, antibacterial, and antiallergic properties. This study aimed to formulate an organic lotion based on mangosteen peel extract and evaluate its physical characteristics and skin pH compatibility. The lotion formulations were prepared using the following ingredients: mangosteen peel extract, tea, stearic acid, cetyl alcohol, glycerin, propyl paraben, methyl paraben, strawberry fragrance, and distilled water. The resulting product exhibited typical organoleptic properties of a lotion, including appropriate texture, color, and odor, and was classified as an oil-in-water (O/W) emulsion type. pH evaluation revealed that formulation 2 had a pH value of 5, which falls within the safe range for human skin, compared to formulation 1 (pH 4) and formulation 3 (pH 6). Therefore, formulation 2 was identified as the most suitable in terms of skin pH compatibility. However, further evaluations—including adhesion, spreadability, viscosity, microbiological, and effectiveness tests—are required before the product can be considered ready for commercialization.